Platelet Rich Fibrin (PRF) and Its Applications in Dentistry: A Review (Academia Journal of Medicine, 2025)
Platelet-rich fibrin has emerged as an innovative biomaterial in dentistry, known for its  regenerative properties that facilitate healing in various oral procedures. This review  examines PRF’s clinical applications, efficacy, and mechanisms of action in dental  treatments, including oral surgery, periodontics, and implantology. PRF is derived from  the patient’s own blood, enhancing biocompatibility and reducing the risk of adverse  reactions. Current research indicates that PRF contributes to improved soft and hard  tissue healing, reduces postoperative complications, and enhances implant stability.  Despite its promising potential, challenges such as variability in preparation protocols  and the need for standardized clinical guidelines persist. This review advocates for  continued research to optimize PRF application and to establish best practices in dental  medicine.
Keywords: PRF; Blood; Platelet Rich Fibrin; Dental Application